The components of Tagetes minuta L. and its biological activities against malaria vector, Anopheles stephensi in Iran - SE Sadat Ebrahimi; A Hadjiakhoondi; Sh Rezazadeh; N Fereidunian; H Vatandoost; MR Abaee (Institue of Medicinal Plants, ACECR, 2005)
Background: Tajetes minuta L. is a native plant of southern America. This plant was distributed from the native region to the other parts of the world. T.minuta L. is being used for its insect's repellency effect and as a food additive by native people especially in southern America and eastern Africa. There are some reports on this plant but not about its larvicide effect. Materials and methods: In the present study hexane extract of the plant was prepared using maceration method. Solvent was evaporated in vacu. The hexane extract was analyzed by GC/MS. Also larvicidal effect of this extract was evaluated against Anopheles stephensi larvae's. Results: The yield of volatile oil using hexane as extraction solvent was 2.6%. Sixteen compounds comprising 93.4% of total extract were identified. The main component was cis --Ocimene (46.39%). The effectiveness of different concentrations of this extract was evaluated against 4th instar larvae of Anopheles stephensi. Results showed that LC50 and LC90 values of volatile oil of T.minuta L. are 3.16 and 11.92 mg/l respectively. Conclusion: Recovery of hexane extract is higher than steam distillation related to total oil and major component (cis --Ocimene) concentration. LC50 and LC90 of hexane extract against larvae were higher than oil prepared with steam distillation method.